Operative fusion of patients with metabolic syndrome increases risk for perioperative complications. (February 2020) - Pierce, Katherine E.; Kapadia, Bhaveen H.; Bortz, Cole; Brown, Avery; Alas, Haddy; Naessig, Sara; Ahmad, Waleed; Vasquez-Montes, Dennis; Manning, Jordan; Wang, Erik; Maglaras, Constance; Raman, Tina; et al.
Highlights: Examined outcomes in spine fusion patients with a diagnosis of metabolic syndrome. Patients were propensity score matched for total levels fused. Patients with metabolic syndrome underwent more posterior and open surgeries. Metabolic syndrome was an independent risk factor for postoperative complications. Abstract: Metabolic syndrome is a clustering of clinical findings defined in the literature including hypertension, high glucose, abdominal obesity, high triglyceride, and low high-density lipoprotein cholesterol levels. The purpose of this study was to assess perioperative outcomes in patients undergoing spine fusion surgery with (MetS) and without (no-MetS) a history of metabolic syndrome. Included: Patients ≥18 yrs old undergoing spine fusion procedures diagnosed with MetS components with BL and 1-year follow-up were isolated in a single-center database. Patients in the two groups were propensity score matched for levels fused. 250 spine fusion patients (58 yrs, 52.2%F, 39.0 kg/m 2 ) with an average CCI of 1.92 were analyzed. 125 patients were classified with MetS (60.2 yrs, 52%F, CCI: 3.2). MetS patients were significantly older (p = 0.012). MetS patients underwent significantly more open (Met-S: 78.4% vs No-MetS: 45.6%, p < 0.001) and posterior approached procedures (Met-S: 60.8% vs No-MetS: 47.2%, p = 0.031). Mean operative time: 272.4 ± 150 min (MetS: 288.1 min vs. no-MetS: 259.7; p = 0.089). Average length of stay: 4.6 days (MetS: 5.27 vs no-MetS: 3.95; p = 0.095). MetS patients had more post-operative complications (29.6% vs. 18.4%; p = 0.038), specifically neuro (6.4% vs 2.4%), pulmonary (4% vs. 1.6%), and urinary (4.8% vs 2.4%) complications. Binary logistic regression analyses found that MetS was an independent risk factor for post-operative complications (OR: 1.865 [1.030–3.375], p = 0.040). With longer surgeries and greater open-exposure types, MetS patients were at greater risk for complications, despite controlling for total number of levels fused. Surgeons should be aware of the increased threat to spine surgery patients with metabolic syndrome in order to optimize surgical decision-making.